2017
DOI: 10.1021/acs.jpcc.7b00258
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Ionic Diodes Demonstrated in Conical Nanopores

Abstract: Ionic transport at the nanoscale features phenomena that are not observed in larger systems. Nonlinear current− voltage curves characteristic of ionic diodes as well as ion selectivity are examples of effects observed at the nanoscale. Many manmade nanopore systems are inspired by biological channels in a cell membrane, thus measurements are often performed in aqueous solutions. Consequently, much less is known about ionic transport in nonaqueous systems, especially in solid-state electrolytes. Here we show io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 59 publications
(108 reference statements)
5
33
0
Order By: Relevance
“…Solid‐state nanochannels/nanopores are adopted widely to simulate the ionic transport in biological systems, and various applications proposed, recently. The latter includes, for example, ionic gates [1, 2], nanofluidic diodes [3–6], energy conversion [7, 8], and filtration/desalination [9, 10]. The phenomena and mechanisms associated with nanochannels/nanopores rest mainly on the nonuniform distribution of ion species and the overlapping of the electric double layer (EDL) in their interior [11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid‐state nanochannels/nanopores are adopted widely to simulate the ionic transport in biological systems, and various applications proposed, recently. The latter includes, for example, ionic gates [1, 2], nanofluidic diodes [3–6], energy conversion [7, 8], and filtration/desalination [9, 10]. The phenomena and mechanisms associated with nanochannels/nanopores rest mainly on the nonuniform distribution of ion species and the overlapping of the electric double layer (EDL) in their interior [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…ICR, an asymmetric current‐voltage behavior when the potential polarity is switched, has been identified in several logic nanofluidic devices [1–6]. Through many experimental and theoretical studies conducted in the last decades, it has been concluded that the ICR phenomenon of nanochannels/nanopores can be attributed to their asymmetric characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the ionic diode field is dominatd by nanochannel [12], nanocone [13,14], and nanopore [15,16] devices that mimic much more closely the biological ion channels located in membranes [17]. A wide range of nano-architectures [18,19] and applications [20] has been proposed, pHswitchable devices have been developed [21], and a perspectives review has appeared with focus on stimuli response "iontronics" [22].…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, inorganic salts (e.g., KCl and NaCl) in aqueous solutions have been used. Siwy and co-workers have considered the case of ionic liquids, aprotic solvents, and solid-state electrolytes [20][21][22].…”
Section: Introductionmentioning
confidence: 99%